Persistently high HBsAg levels during HBeAg‐seropositive stage predict lower risk of hepatocellular carcinoma in chronic hepatitis B patients - Lin, Hsin‐Che; Jeng, Wen‐Juei; Liu, Jessica; Pan, Mei‐Hung; Lee, Mei‐Hsuan; Batrla‐Utermann, Richard; Lu, Sheng‐Nan; Chen, Chuen‐Fei; Yang, Hwai‐I.; Chen, Chien‐Jen (Alimentary pharmacology & therapeutics, 2024)
Summary Background High hepatitis B surface antigen (HBsAg) level predicts hepatocellular carcinoma (HCC) in chronic hepatitis B (CHB) patients with low viral load. The role of longitudinal HBsAg levels in predicting HCC in HBeAg‐positive CHB patients remains unknown. Method HBeAg‐positive CHB participants from the REVEAL‐HBV cohort with ≥2 HBsAg measurements before HBeAg seroclearance were enrolled. Group‐based trajectory modelling identified distinct HBsAg trajectory groups during a median of 11 years of HBeAg‐positive status. Cox regression models were applied for investigating independent predictors of HCC and estimating adjusted hazard ratio (HRadj) with a 95% confidence interval (CI). A p‐value less than 0.05 was considered statistically significant. Results A total of 319 patients were enrolled and classified by HBsAg trajectory patterns as (A) persistently high group (n = 72): HBsAg persistently ≥104 IU/mL, and (B) non‐stationary group (n = 233): low HBsAg at baseline or declining to <104 IU/mL during the follow‐up. Group B had higher proportions of abnormal ALT levels, HBV genotype C and basal core mutation than group A (p < 0.05); age at entry and gender were comparable. The annual incidence of HCC in group A and group B were 0.37% and 1.16%, respectively (p = 0.03). In multivariate analysis, age >40 years (HRadj [95% CI] = 4.11 [2.26–7.48]), genotype C (HRadj [95% CI] = 4.39 [1.96–9.81]) and the non‐stationary group (HRadj [95% CI] = 3.50 [1.49–8.21]) were independent predictors of HCC. Basal core promoter mutation was the only risk factor of HCC in the persistently high HBsAg group (HRadj [95% CI] = 32.75 [5.41–198.42]). Conclusion Patients with persistently high HBsAg levels during HBeAg‐seropositive stage represent a unique population with low risk of HCC development. Persistent high HBsAg levels during HBeAg‐seropositive stage predicts lower risk of hepatocellular carcinoma in chronic hepatitis B patients